Smart mobile application for resume building and career advisory services - Leong, Ming Shan (2025)
The increasing complexity for the current modern job market trend has clearly stated that the importance of professional resumes and career advisory services for job seekers no matter students, graduates, and professionals. By reviewing the current mobile resume building applications, it shows that these applications often lack AI functionality, integration of career advisory features, and sufficient customization options which limits user effectiveness. To address these issues, this project aims to develop a smart Android mobile application, Job Assistant, with integrates Google Gemini AI model for main features. The project follows Scrum methodology framework by conducting the requirement analysis, project designs, development, testing and deployment across five sprints. The developed application used Android Studio, React Native, Visual Studio Code, SQLite database, and integrated Gemini AI by using API key for supporting the professional resume creation and personalized career advice recommendations. The developed key features include resume creation with AI-powered, AI generation career advisory services and various customizable options for resumes. Testing with unit test and UAT gained an overall good result with overall unit test cases passed and UAT 4.82 over 5 rating. These findings highlight that integration of AI into resume-building tools not only increases efficiency but also strengthens user job opportunities with supporting career decisions. To conclude, this project, the smart mobile application with resume building and career advisory services which called Job Assistant represents a valuable community initiative software solution that supports equal access to career development resources and align with Sustainable Development Goals (SDG) such as decent work and no poverty. This Android mobile application can be further expanded with features like multi-languages support, integration with job platforms, iOS version release, offline AI functionality and others to maximize and improve this application.